SEPARATION OF P-HYDROXYBENZOIC ACID ALKALI SALT - IJIRI MAKIKO; SUZUKI TOSHINOBU; MATSUURA AKINORI; SAIMA HITOSHI (1991)
PURPOSE:To easily separate the subject compound in high purity without generating emulsion by reacting a phenol alkali with carbon dioxide and washing the reaction product with a specific oxygen-containing compound other than carboxylic acid. CONSTITUTION:A p-hydroxybenzoic acid alkali salt useful as an intermediate for liquid crystal resin or pharmaceuticals is produced by the Kolbe-Schmitt reaction of a phenol alkali or a mixture containing the compound and carbon dioxide. The reaction product is washed with >=0.1 pts.wt., preferably 1-100 pts.wt. (based on 1 pt.wt. of the reaction product) of a <=10C oxygen-containing compound other than carboxylic acid (e.g. acetone) to remove the reaction medium and by-produced salicylic acids and phenols at the same time from the reaction product without using a liquid-liquid separation process liable to generate an emulsion. The objective compound can be easily separated by this process in high purity.